Effectiveness of Milk as A Desensitizing Agent in Dentin Hypersensitivity After Nonsurgical Periodontal Treatment - Kristina Silaban; Martina Amalia; Rini Octavia Nasution (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Dentin hypersensitivity (DH) is the most common clinical problem after nonsurgical periodontal treatment. It is characterized by sharp pain or discomfort arising in response to thermal, chemical, or osmotic stimuli due to exposure to dentin after enamel or cementum on the root surface that is lost in periodontal treatment. This can complicate the patient's plaque control and lead to failure of periodontal treatment. This paper aims to evaluate the effectiveness of milk as a desensitizing agent for DH treatment after nonsurgical periodontal treatment. Literature Review: DH is the movement of fluid within the dentinal tubules stimulating A-delta fibers resulting in localized sharp pain based on Brannstrom's Hydrodynamic Theory. Milk contains casein phosphoprotein (CPP) where the phosphosaryl sequence attaches to the amorphous calcium phosphate (ACP) of teeth and forms CPP-ACP bonds so as to prevent the loss of calcium and phosphate ions and re-form apatite crystals which is a mechanism of dental desensitization. The results of Sabir and Alam's research found that gargling with milk can provide calcium and phosphate bioavailability which can help remineralize open dentin tubules so as to reduce DH. After nonsurgical periodontal treatment, milk can be used as a desensitizing agent and gargling with milk for several days effectively reduces DH quickly. Conclusions: The use of milk as a desensitizing agent can result in a significant decrease in DH after nonsurgical periodontal treatment. Milk is also easy to come by, cheap, works fast, and can be used at home for DH issues.